Model Konseling Karir Integratif Berbasis Digital untuk Meningkatkan Employability Skill Mahasiswa Universitas Sains Cut Nyak Dhien - Rizki, Dina; Sari, Meylia (At-Taujih : Bimbingan dan Konseling Islam, 2026)
Final year students in particular experience low self-confidence and a lack of preparedness to face the world of work. This condition indicates that students' employability skill  s still need to be developed through career counseling services that are more adaptive and in line with developments in digital technology. This study aims to analyze the implementation of digital-based integrative career counseling in improving the employability skill  s of final year students at Cut Nyak Dhien University of Science. This study uses a qualitative descriptive approach with 10 final year students as research subjects. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions to find the main themes related to changes in students' employability skill  s after participating in digital-based integrative career counseling. The results of the study indicate that digital-based integrative career counseling can help students identify career problems, understand interests and talents, and increase readiness to face the world of work. The counseling process is carried out through an integration of cognitive-behavioral, humanistic, and solution-based approaches supported by the use of digital media as a means of communication and career exploration. The research findings indicate four key changes in students: increased self-awareness, increased confidence in career choices, the ability to develop more realistic career plans, and increased preparedness for the world of work. Furthermore, students also demonstrated improved employability skill  s in communication, adaptability, decision-making, and digital literacy. Keywords: Integrative Career Counseling, Digital, Employability skill